External shocks, internal shots: The geography of civil conflicts - Nicolas Berman; Mathieu Couttenier (Graduate Institute of International and Development Studies, 2012)
This paper uses detailed information on the latitude and longitude of conflict events within a set of Sub-Saharan African countries to study the impact of external income shocks on the likelihood of violence. We consider a number of external demand shocks faced by the country or the regions within countries - changes in the world demand of agricultural commodities, financial crises in the partner countries or changes in foreign trade policy - and combine these with information reflecting the natural level of trade openness of the location. We find that (i) within-country, the incidence, intensity and onset of conflicts are generally negatively and significantly correlated with income shocks within locations; (ii) this relationship is significantly weaker for the most remote locations, i.e those located away from the main seaports, (iii) at country-level, we cannot detect any significant effect of these shock on conflict incidence or onset; but (iv) large and longlasting shocks seem to affect the location of conflict outbreaks. In general, our results suggest that external income shocks are important determinants of the intensity and geography of conflicts within countries. However, conflicts tend to start in remote locations which are naturally less affected by foreign shocks, which might explain why these seem to have little effect on conflict onset at the country-level.
Keywords: D74; F15; O13; Q17; 330; conflict; income shock; civil war; Agraraußenhandel; Gesamtwirtschaftliche Nachfrage; Schock; Bürgerkrieg; Afrika südlich der Sahara